Postmenopausal Hormone Use and the Risk of Nephrolithiasis: Results From the Women’s Health Initiative Hormone Therapy Trials - Maalouf, Naim M. (2010)
BACKGROUND: Observational studies examining the role of estrogen in the risk of kidney stone formation have shown conflicting results. However, randomized trial evidence on nephrolithiasis risk with estrogen therapy in postmenopausal women is lacking. METHODS: We reviewed the incidence of nephrolithiasis in the Women’s Health Initiative estrogen-alone and estrogen plus progestin trials conducted at 40 US clinical centers. A total of 10 739 postmenopausal women with hysterectomy were randomized to receive 0.625 mg/d of conjugated equine estrogens (CEE) or placebo, and 16 608 postmenopausal women without hysterectomy were randomized to receive placebo or estrogen plus progestin given as CEE plus medroxyprogesterone acetate (2.5 mg/d). The incidence of nephrolithiasis was determined for an average follow-up of 7.1 years for the CEE trial and 5.6 years for the estrogen plus progestin trial. RESULTS: Baseline demographic characteristics and risk factors for nephrolithiasis were similar in the placebo and treatment arms. Estrogen therapy was associated with a significant increase in nephrolithiasis risk from 34 to 39 cases per 10 000 person-years (hazard ratio, 1.21; 95% confidence interval, 1.03-1.44). Censoring data from women when they ceased to adhere to study medication increased the hazard ratio to 1.39 (95% confidence interval, 1.08-1.78). The increased nephrolithiasis risk was independent of progestin coadministration, and effects did not vary significantly according to prerandomization history of nephrolithiasis. CONCLUSIONS: These data suggest that estrogen therapy increases the risk of nephrolithiasis in healthy postmenopausal women. These findings should be considered in decision making regarding postmenopausal estrogen use. The mechanisms underlying this higher susceptibility remain to be determined.